IT IS TRAMPLED BY THE KNEE-BOOT OF INVADER (Preface «Talent-self-taught person with Pereginsk» V.V. Ganushchak) - Kostyuk, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the question is life creation of poet with Pereginsk on PreCarpathians of Osip Moshura (1909-1942).